Deviation of Spatial Representation and Asymmetric Saccadic Reaction Time in Hemi-Parkinson’s Disease - Shen, Dongfang; Li, Min; Zhou, Ying; Liang, Lixin; Zhang, Lu; Zhang, Wangzikang; Zhang, Mingsha; Pan, Yujun (Frontiers in Aging Neuroscience, 2018)
Background: Patients with Parkinson’s disease (PD) commonly show spatially asymmetric behaviors, such as veering while attempting to walk in a straight line. While there is general agreement that the lateral motor dysfunction contributes to asymmetric behaviors in PD, it is dispute regarding whether the spatial perception is also biased. In addition, it is not clear whether PD impairs the speed of spatial information process, i.e., the efficiency of information process. Objectives: To assess the visuospatial representation and efficiency of spatial information processing in hemi-PD. Methods: Two saccadic tasks were employed: non-spatial cue evoked saccade and spatial cue evoked saccade. In the former task, an identical visual stimulus (appeared on the body mid-sagittal plane) was artificially associated with a fixed saccadic target (left or right) in a given session. In the latter task, subjects were instructed to make a rightward or leftward saccade based on the perceived location of a visual cue (left versus right side of the body mid-sagittal plane). We estimated the location of subjective straight ahead (SSA) for each subject by using a psychometric fitting function to fit the location judgment results, enabling evaluation of the symmetry of representation between the left and right hemifields. In addition, since the locations of saccadic targets were same in these two tasks, thus, for each individual subject, the elongated saccadic reaction time (SRT) in the latter task, comparing with the former one, mainly reflects the time spent on judgment of the spatial location of visual cue, i.e., spatial perception. We also assessed the efficiency of spatial perception between two hemispheres, through comparing the normalized SRT (i.e., SRT difference between two tasks) between trials with leftward and rightward judgments. Results: Compared with healthy control subjects (HCs), the SSA was shifted to the contralesional side in both left onset PD (LPD, lesion of right substantia nigra) and right onset PD (RPD, lesion of left substantia nigra) patients. The process of spatial information was significantly longer when a spatial cue appeared in the contralesional hemifield. Conclusions: Patients with hemi-PD showed biased visuospatial representation between left and right hemifields and decreased the efficiency of spatial